2014
DOI: 10.1523/jneurosci.0805-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of Associative Memories in Early Visual Cortex Is Signaled by the Hippocampus

Abstract: The cortical reinstatement hypothesis of memory retrieval posits that content-specific cortical activity at encoding is reinstated at retrieval. Evidence for cortical reinstatement was found in higher-order sensory regions, reflecting reactivation of complex object-based information. However, it remains unclear whether the same detailed sensory, feature-based information perceived during encoding is subsequently reinstated in early sensory cortex and what the role of the hippocampus is in this process. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
135
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 65 publications
15
135
1
Order By: Relevance
“…Furthermore, fMRI studies have revealed predictive signals in the hippocampus (13,26,27), and Reddy et al (28) reported anticipatory firing to expected stimuli in the medial temporal lobe, including the hippocampus. One intriguing possibility is that predictive signals from the hippocampus are fed back to sensory cortex (13,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fMRI studies have revealed predictive signals in the hippocampus (13,26,27), and Reddy et al (28) reported anticipatory firing to expected stimuli in the medial temporal lobe, including the hippocampus. One intriguing possibility is that predictive signals from the hippocampus are fed back to sensory cortex (13,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that stimulus-specific scene patterns were reactivated in the parahippocampal cortex when participants indicated they had recollected the target scene, but not when they indicated they had no recollection (Fig. 2) (Staresina et al 2012; see also, Ritchey et al 2008;Bosch et al 2014). This is an important step toward demonstrating that episodic reinstatement in the MTL can be observed at the level of individual memory representations.…”
Section: Multivariate Fmri and Connectivity Analyses Of Episodic Retrmentioning
confidence: 90%
“…On the other hand, only a few studies have addressed how content-general memory processes promote the distributed reactivation of stimulus-specific patterns during memory retrieval, and most studies have focused on a narrow subset of brain regions. For example, hippocampal activation has been shown to promote the cortical reinstatement of scene-specific (Ritchey et al, 2013) and categorical source information (such as faces vs. scenes; Gordon et al, 2013) and of low-level visual gratings (Bosch, Jehee, Fernandez, & Doeller, 2014).…”
Section: Introductionmentioning
confidence: 99%